Recent Findings in Alzheimer Disease and Nutrition Focusing on Epigenetics. - Athanasopoulos, Dimitrios; Karagiannis, George; Tsolaki, Magda (Advances in Nutrition, 2016)
Alzheimer disease (AD) is a chronic neurodegenerative disease with no effective cure so far. The current review focuses on the epigenetic mechanisms of AD and how nutrition can influence the course of this disease through regulation of gene expression, according to the latest scientific findings. The search strategy was the use of scientific databases such as PubMed and Scopus in order to find relative research or review articles published in the years 2012-2015. By showing the latest data of various nutritional compounds, this study aims to stimulate the scientific community to recognize the value of nutrition in this subject. Epigenetics is becoming a very attractive subject for researchers because it can shed light on unknown aspects of complex diseases like AD. DNA methylation, histone modifications, and microRNAs are the principal epigenetic mechanisms involved in AD pathophysiology. Nutrition is an environmental factor that is related to AD through epigenetic pathways. Vitamin B-12, for instance, can alter the one-carbon metabolism and thus interfere in the DNA methylation process. The research results might seem ambiguous about the clinical role of nutrition, but there is strengthening evidence that proper nutrition can not only change epigenetic biomarker levels but also prevent the development of late-onset AD and attenuate cognition deficit. Nutrition might grow to become a preventive and even therapeutic alternative against AD, especially if combined with other antidementia interventions, brain exercise, physical training, etc. Epigenetic biomarkers can be a very helpful tool to help researchers find the exact nutrients needed to create specific remedies, and perhaps the same biomarkers can be used even in patient screening in the future.